Immunometabolism in the pathogenesis of vitiligo - Lyu, Chen; Sun, Yonghu (Frontiers in Immunology, 2022)
Vitiligo is a common depigmenting skin disorder characterized by the selective loss of melanocytes. Autoimmunity, genetic, environmental, and biochemical etiology have been proposed in vitiligo pathogenesis. However, the exact molecular mechanisms of vitiligo development and progression are unclear, particularly for immunometabolism. Sporadic studies have suggested mitochondrial dysfunction, enhanced oxidative stress, and specific defects in other metabolic pathways can promote dysregulation of innate and adaptive immune responses in vitiligo. These abnormalities appear to be driven by genetic and epigenetic factors modulated by stochastic events. In addition, glucose and lipid abnormalities in metabolism have been associated with vitiligo. Specific skin cell populations are also involved in the critical role of dysregulation of metabolic pathways, including melanocytes, keratinocytes, and tissue-resident memory T cells in vitiligo pathogenesis. Novel therapeutic treatments are also raised based on the abnormalities of immunometabolism. This review summarizes the current knowledge on immunometabolism reprogramming in the pathogenesis of vitiligo and novel treatment options.